The British Building Guilds: A Critical Survey of Two Years' Work - Joslyn, Carl S. (Quarterly Journal of Economics, 1922)
Social and industrial background; structure of the guilds, 80. — Distribution of function and control, 85. — Guild principles: "organized public service, " the Guild form of contract, Guild workmanship, workers' control, continuous pay and remuneration, 90. — Credit, finance, and insurance; relations with the C. W. S.; the Guild's financial record, 100. — Experience of the guilds: competitive tendering; the Guild's challenge; continuous pay costs; comparative labor efficiency; building costs on Guild contracts; the quality of Guild workmanship; Guild discipline and employment management; progress of the Guild movement, 106. — Conclusions: as to the building guilds; as to Guild Socialism in general, 127.